Effects of dietary gelatin hydrolysates on bone mineral density in magnesium-deficient rats - Teruyuki Noma (BMC Musculoskeletal Disorders, 2017)
Abstract Background The major types of commercially available gelatin hydrolysates are prepared from mammals or fish. Dietary gelatin hydrolysates from mammals were reported to improve bone mineral density (BMD) in some animal models. In contrast, there is limited study showing the effects of dietary gelatin hydrolysates from fish on BMD. The quantity and structure of peptides in the plasma after oral administration of gelatin hydrolysates depend on the gelatin source, which suggests that the biological activity of gelatin hydrolysates depend on the gelatin source. This study examined the effects of fish-derived gelatin hydrolysate (FGH) or porcine-derived gelatin hydrolysate (PGH) intake on BMD and intrinsic biomechanical properties in magnesium (Mg)-deficient rats as a model showing the decrease in both BMD and intrinsic biomechanical properties. Methods Four-week-old male Wistar rats were assigned into four groups: a normal group was fed a normal diet (48 mg Mg/100 g diet), a Mg-deficient (MgD) group was fed a MgD diet (7 mg Mg/100 g diet), a FGH group was fed a MgD + FGH diet (5% FGH), and a PGH group was fed a MgD + PGH diet (5% PGH) for 8 weeks. At the end of the study, BMD and intrinsic biomechanical properties of the femur were measured. Results The MgD group showed significantly lower Young’s modulus, an intrinsic biomechanical property, and trabecular BMD of the femur than the normal group; however, the MgD diet did not affect cortical BMD and cortical thickness. Both the FGH and the PGH groups showed significantly higher cortical thickness and ultimate displacement of the femur than the normal group, but neither type of gelatin hydrolysate affected Young’s modulus. Furthermore, the FGH group, but not the PGH group, showed significantly higher trabecular BMD than the MgD group. Conclusions This study indicates that FGH and PGH increase cortical thickness but only FGH prevents the decrease in trabecular BMD seen in Mg-deficient rats, while neither type of gelatin hydrolysate affect intrinsic biomechanical properties.